"Being strong enough to defend yourself": untangling the Women, Peace and Security agenda amidst the Ukrainian conflict. Issue 5 (20th October 2019) - O'Sullivan, Mila
ABSTRACT: Following the outbreak of armed conflict in 2014, Ukraine adopted a National Action Plan within United Nations Security Council Resolution 1325 for the period 2016–20, the first country in conflict to do so. Ukraine's case demonstrates that in a situation of active conflict, the Women, Peace and Security (WPS) agenda becomes strongly linked to military security. Drawing on interviews, documents, and narratives by feminist and public figures, I argue that the WPS agenda in Ukraine has taken a narrow militarized form as a result of a combination of three interrelated and mutually constitutive factors: the ongoing conflict, nationalistic feminism, and the role of international organizations. The open conflict has generated a militaristic and nationalistic discourse among mainstream Ukrainians with an emphasis on defending the country. This discourse has been translated by international organizations and national actors into the WPS agenda, which has prioritized security sector reforms. Implementation of the WPS agenda in Ukraine therefore seems to be at odds with this norm's feminist principles. It is not leading to peace but to militarization, neglecting broader insecurities, including socioeconomic inequalities that have, in turn, been exacerbated by the conflict and the state's institutional reforms.